2007
DOI: 10.1080/13651500600973568
|View full text |Cite
|
Sign up to set email alerts
|

Partial compliance with antipsychotics and its impact on patient outcomes

Abstract: Partial compliance with antipsychotic medications is a common and complex phenomenon that is underestimated by physicians. The consequences of partial compliance include an increased risk of relapse, rehospitalization and suicide attempts. Stigma, negative attitudes towards medications, cognitive impairment and diminished insight negatively impact treatment adherence. Oral atypical antipsychotics may improve both insight and cognitive function, but compliance with these agents is not assured. Depot conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…Regular medication helps to stabilize the illness, and research has shown that better drug compliance results in a lower re‐hospitalization rate and improves both insight and cognitive function (Narasimhan et al . 2007, Llorca 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Regular medication helps to stabilize the illness, and research has shown that better drug compliance results in a lower re‐hospitalization rate and improves both insight and cognitive function (Narasimhan et al . 2007, Llorca 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, medication non-adherence is a major factor for the recurrence of psychiatric symptoms, relapse, and re-hospitalization (McCann, Boardman, & Clark, 2008). Even partial adherence to psychotropic medication can result in negative outcomes, including symptom exacerbation, suicidal ideation, and suicide attempts (Narasimhan, Pae, Masand, & Masand, 2007). Considering the clinical consequences of poor medication adherence in psychiatric patients, research has shown that the principles of Motivational Interviewing (MI) can be used in clinical practice to improve patients' attitudes and insight as well as their adherence to treatment (Tay, 2007;Rusch & Corrigan, 2002).…”
mentioning
confidence: 99%
“…Efficacy. The CATIE project found that 24% of discontinuation was caused by lack of efficacy (Narasimhan, Pae, Masand, & Masand, 2007).…”
mentioning
confidence: 99%